Perspektif Islam Tentang Kepemimpinan Perempuan Pada Lembaga Pendidikan - Norma Fitria (Departement of Mathematics Education, 2023)
The background of this research is the importance of studying Islamic perspectives on women's leadership in educational institutions. Given that currently many educational institutions are led by a female leader and these educational institutions are successful. The purpose of this study was to find out the Islamic perspective on women's leadership in educational institutions. The method used in this study is a library approach. The results of the study show that leadership is now more dependent on the physical and mental readiness of both men and women in a planned direction towards professionalism rather than just the skills, heritage, experience and mentality of men. To produce good quality leadership, all programs must go through a systematic process of planning, analysis and development. So as to create an appropriate leadership perspective Islam. The conclusion of this study is that women's leadership competencies can also create effective leadership in educational institutions.